Identification of novel compounds against Trypanosoma cruzi using AlphaFold structures - Albert Ros-Lucas; Alejandra Saeteros; Juan Carlos Gabaldón-Figueira; Nieves Martínez-Peinado; Elisa Escabia; Joaquim Gascón; Julio Alonso-Padilla (Computational and Structural Biotechnology Journal)
Chagas disease is a neglected tropical zoonosis caused by the protozoan Trypanosoma cruzi. The two approved medications for treating this disease show variable efficacy in the chronic phase, highlighting the need for new therapeutic interventions. This study explores a bioinformatics-driven approach to drug discovery using AlphaFold-predicted protein structures. Starting from a virtual screening of approximately 30,000 compounds, 24 were experimentally tested, and two already approved drugs, pimecrolimus and ledipasvir, demonstrated significant antiparasitic activity. These compounds were predicted to target previously uncharacterized T. cruzi proteins, ledipasvir interacting with a calpain-like protein and pimecrolimus likely binding a mitotic cyclin. Molecular dynamics simulations showed that pimecrolimus remains stable in the predicted binding site, while ledipasvir exhibits a higher RMSD. While experimental validation of these targets is needed, these findings underscore the potential of integrating AlphaFold structures into drug discovery strategies to accelerate the identification of new compounds against Chagas disease and other neglected tropical diseases. Summary: We performed a virtual screening experiment with T. cruzi AlphaFold protein models and a compound collection of more than 30,000 compounds. We tested the top ranked compounds in an in vitro setting, and found two promising candidates for drug repurposing against Chagas disease: pimecrolimus and ledipasvir.